Overview on Current Trends and Emerging Therapies in the Chemotherapy of Patients with Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer: Trends and Emerging Therapies in Chemotherapy of HER2-positive BC - Qian, Jian; Xu, Yunxia; Ling, Xiaokai; Wang, Fenhua (Galen Medical Journal, 2023)
Over the past few decades, significant progress has been made in the management of hu-man epidermal growth factor receptor 2 (HER2)-positive breast cancer (BC) due to the de-velopment of targeted therapies. However, HER2-positive BC is an aggressive subtype, posing significant challenges, including treatment resistance and disease recurrence. Cur-rent standard treatment options for HER2-positive BC include combinations of chemother-apy drugs, targeted therapies such as trastuzumab and pertuzumab, and hormone therapies. However, some important limitations of these treatments, such as resistance and adverse effects, are reported. Also, we showed emerging therapeutic options, such as novel chemo-therapy agents, antibody-drug conjugates, and immune checkpoint inhibitors, and discussed their mechanisms of action, potential benefits, and potential future directions in the field.